Prevalence of elevated liver enzymes in adults with type 1 diabetes: A multicentre analysis of the German/Austrian DPV database. Issue 8 (10th April 2017) - Stadler, Marietta; Bollow, Esther; Fritsch, Maria; Kerner, Wolfgang; Schuetz‐Fuhrmann, Ingrid; Krakow, Dietmar; Merger, Sigrun; Riedl, Michaela; Jehle, Peter; Holl, Reinhard W.; ,
Abstract : Aims: To assess the prevalence of elevated liver enzymes in adults with type 1 diabetes mellitus (T1DM) in routine clinical care and the association with cardiovascular risk profile in the Diabetes‐Prospective‐Documentation (DPV) network in Germany and Austria. Subjects and methods: This cross sectional observational study from the DPV registry includes data from 45 519 adults with T1DM at 478 centres up to September 2016. Liver enzyme measurements were available in 9226 (29%) patients at 270 centres and were analysed for increased alanine aminotransferase (ALT; men >50 U/L, women >35U/L) and/or aspartate aminotransferase (AST; men >50 U/L, women >35U/L) and/or gamma‐glutamyltransferase (GGT; men >60U/L, women >40 U/L). A subgroup analysis in patients for whom 2 or more ALT measurements were available (n = 2335, 25%) and whose ALT was increased at least twice (men >30 U/L, women >19U/L) was performed. Associations with glycaemic control, cardiovascular risk factors and late complications were investigated with multiple regression analyses. Results: Twenty percent (19.8%, n = 1824) had increased liver enzyme(s) on one or more occasions. Increased liver enzymes were associated with worse glycaemic control and higher BMI (both P  < .0001), dyslipidemia (OR, 1.75; 95% CI, 1.54‐2.0), hypertension (OR, 1.48; 95% CI: 1.31‐1.68), myocardial infarction (OR, 1.49; 95% CI, 1.17‐1.91) and end stage renal disease (OR, 1.59; 95% CI, 1.17‐2.17). ALT was increased twice in 29% and was associated with worse glycaemic control ( P  < .0001), higher BMI ( P  < .0001), hypertension (OR, 1.58; 95% CI, 1.26‐1.97) and dyslipidemia (OR, 1.89; 95% CI, 1.51‐2.37). Conclusions: In this clinical audit in adults with T1DM, elevated liver enzymes on routine assessment were associated with a less favourable cardiovascular risk profile and with poorer glycaemic control.